Toward a Topology-Based Therapeutic Design of Membrane Proteins: Validation of NaPi2b Topology in Live Ovarian Cancer Cells - Bulatova, Leisan; Savenkova, Daria; Nurgalieva, Alsina; Reshetnikova, Daria; Timonina, Arina; Skripova, Vera; Bogdanov, Mikhail; Kiyamova, Ramziya (Frontiers in Molecular Biosciences, 2022)
NaPi2b is a sodium-dependent phosphate transporter that belongs to the SLC34 family of transporters which mainly responsible for phosphate homeostasis in humans. Although NaPi2b is widely expressed in normal tissues, its overexpression has been demonstrated in ovarian, lung and other cancers. A valuable set of antibodies including L2(20/3) and MX35 and its humanized versions react strongly with an antigen on the surface of ovarian and other carcinoma cells. Although the topology of NaPi2b was predicted in silico, no direct experimental data are available for the orientation of NaPi2b extracellular domains in cancer cells. Presented results of antibody mapping of untagged NaPi2b in live ovarian carcinoma cells OVCAR-4 provide a platform for current and future epitope-based cancer therapy and serological diagnostics.